Edge Detection Using Circular Sliding Window - Al-Zuky, A.A. D.; Al-Taa’y, H. J. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper, we devoted to use circular shape sliding block, in image edge determination. The circular blocks have symmetrical properties in all directions for the mask points around the central mask point. Therefore, the introduced method is efficient to be use in detecting image edges, in all directions curved edges, and lines. The results exhibit a very good performance in detecting image edges, comparing with other edge detectors results.